The effect of hip extension velocity on the association between hip extension torque and sprint horizontal force in elite athletes - Hegyi, A.; Fornasier-Santos, C.; Hollville, E.; Giroux, C.; Leboeuf, F.; Lacourpaille, L.; Nordez, A.; Rabita, G.; Slawinski, J.; Morin, J. B.; Dorel, S.; Hug, F.; et al. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Hip extensors have a major contribution to sprint running propulsion in the early stance phase when glutes and hamstrings shorten at high velocities (1). Considering the difficulties to perform isokinetic testing of this muscle group, hip extensors are typically tested in isometric conditions, which may not reflect the role of hip extensors in sprinting. The aim of this study was to 1) develop a protocol for testing hip extensors in isometric and concentric conditions, and 2) examine the association between hip extension torque measured at different velocities and sprint horizontal force in elite athletes.